A review: 3D printing of microwave absorption ceramics. Issue 6 (16th August 2020) - Wang, Tingting; Lu, Xuefeng; Wang, Ao
Abstract: Along with extensive research on the 3D printing and microwave absorption ceramics, 3D printing technology provides a great possibility for microwave absorption ceramics with arbitrary shapes in a faster, cheaper and more flexible way. This review focuses on the latest evolution in the raw materials, the structure design and the advanced additive manufacturing technologies of 3D printing microwave absorption ceramics. Firstly, the representative raw materials are divided into three categories, including ceramic powder, cermet powder and precursor resin. In addition, additives give rise to improvement of microwave absorption properties of ceramics. Secondly, based on two attenuation theories, structure design makes further efforts to enhance the microwave absorption performance of ceramics. Finally, comparisons are made between diversified manufacturing technologies to facilitate the selection of the best ones for different application in practical use. This study presents a summary of research that has been conducted to produce microwave absorption ceramics by additive manufacturing.